PENERAPAN SP4N-LAPOR PADA SATUAN POLISI PAMONG PRAJA KOTA SAMARINDA - Yusuf, Muhammad; Apriani, Fajar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
SP4N-LAPOR (National Public Service Complaints Management System – People’s Aspiration and Complaints Services) are a national platform designed to manage claims and are designed to make it easier for people to voice complaints and aspirations related to online public services. The purpose of this study is to analyze the application of SP4N-LAPOR in the Samarinda City Civil Service Police Unit and the factors that are a threat to its application. The type of research used is qualitative descriptive with the focus of research on the application of complaints management systems that use indicators of source, process and targets approaches. The data sources come from the primary data, such as the Head of the Samarinda City Civil Service Police Unit as the key informant, the Head of the SP4N-LAPOR Program Management and Application of the Samarinda City Communication and Information Office, as well as the application user community as informants. This research also uses secondary data from reports, archives/report documents sources from the Samarinda City Communication and Information Office and the Samarinda City Civil Service Police Unit. Data collection was carried out using interviews techniques, observations, library research and documentation. Data analysis using an intercative model. The results of this study would suggest that the application of SP4N-LAPOR in the Samarinda City Civil Service Police Unit has gone quite well in improving the quality of public service. The application of this program has been in accordance with the prevailing regulations and is supported by good coordination and direction from leaders. The process of containing complaint runs reasonably well with structured, enabling the Samarinda City Civil Service Police Unit to respond quickly and properly to complaint, in addition to cooperation with other agencies as a factor in its efficiency. However, there are still some obstacles such as internal communication problems, scheduling activities, long procedures for handling reports, the accessibility of applications and websites that are less smooth, the lack of recapitalization of reports and internal evaluations by the Samarinda City Civil Service Police Unit.